2006
DOI: 10.1109/tgrs.2006.879114
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Correlation Functions and Power Spectra in Clouds Using the NRL WARLOC Radar

Abstract: The Naval Research Laboratory W-band Advanced Radar for Low Observable Control (WARLOC) is a highpower 94-GHz radar, with 3-10-kW average and 80-kW peak power, now set up on the western shore of the Chesapeake Bay. It has three orders of magnitude more power and sensitivity than other W-band radar systems. This enables cloud reflectivity to be measured with high signal-to-noise ratios and a resolution of about 15 m over a two (or three)-dimensional region, which can be as large as tens of kilometers on a side.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The expected diurnal peaks at 24 h and harmonics are present. At high frequencies, the plants exhibit a spectrum similar to cloud processes [38,39]. These processes may be a function of the f 5 23°54′N, 71°12′E), has an f 1.76 spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The expected diurnal peaks at 24 h and harmonics are present. At high frequencies, the plants exhibit a spectrum similar to cloud processes [38,39]. These processes may be a function of the f 5 23°54′N, 71°12′E), has an f 1.76 spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…3). Cloud structure can be intricate with significant spatial variations across a single field of view, and can change in the time interval between exposures (Fliflet & Manheimer 2006;Koren et al 2008). In the worst case, the loss of light will be too severe to allow useful data to be taken.…”
Section: Atmospheric Extinction and The Nature Of Cloudsmentioning
confidence: 99%
“…An examination of the power spectra (not shown) indicates there is generally a scale break (below the correlation length scale) where the spectrum behaves as $k À3 to k À1.5 depending on location, while at scales larger than the correlation length the spectrum goes as $k À1.5 to k À1.2 . We noted in section 1 that Fliflet and Manheimer [2006] used a high-power scanning millimeter-wavelength (94 GHz, W band) radar to study the spatial correlation of reflectivity from cirrus clouds and that they found the reflectivity autocorrelation function decreased with scale as r 2/3 (that is, b = 2/3 and equivalent to a wave number spectrum of k À5/3 ) for scale lengths ranging from 30 m to 10 km. Restricting the range from 1 to 10 km, we too find b = $2/3 for midlatitude clouds in the upper troposphere (and b $ 0.5 when fitting over the range 1-200 km).…”
Section: Appendix B: Power Spectrummentioning
confidence: 99%
“…However, the spatial structure of hydrometeor (cloud and precipitation) reflectivity and Doppler velocities from centimeter and millimeter wavelength radar have also been investigated [e.g., Smythe and Zrnic , 1983; Heymsfield , 1976; Lothon et al , 2005]. Fliflet and Manheimer [2006] used a high‐power scanning millimeter‐wavelength (94 GHz, W‐band) radar to study the spatial correlation of reflectivity from cirrus clouds. They found the reflectivity autocorrelation function decreased with scale as r 2/3 (equivalent to a wave number spectrum of k −5/3 ) for scale lengths ranging from 30 m to 10 km.…”
Section: Introductionmentioning
confidence: 99%